Gambling and homelessness in older adults: a qualitative investigation. (12th December 2021) - Vandenberg, Brian; Livingstone, Charles; Carter, Adrian; O'Brien, Kerry
Abstract: Background and Aims: Homelessness is one of the most significant harms associated with gambling and appears to affect older adults disproportionately, but the relationship has received little research attention. This exploratory study investigated how gambling and homelessness is linked in older adults. Methods: Using qualitative research methods, we undertook in‐depth semi structured face‐to‐face individual and group interviews to gather data from a purposive sample ( n = 48) of key informants working in service provision for older adults (aged 50+ years) experiencing gambling‐related harm and/or homelessness in Victoria, Australia. Thematic analysis of data focused on evaluating mechanisms and identifying contextual conditions that activate pathways between gambling and homelessness. Results: The relationship between gambling and homelessness in older adults is often indirect and non‐linear, and can represent a reflexive cycle. Experiencing periods of homelessness into older age can contribute to gambling, often because the adverse impacts of homelessness on older adults' mental and material wellbeing increase the appeal of gambling. Additionally, comorbidities (e.g. substance use, mental illness, past trauma) and structural conditions (e.g. gambling accessibility, poverty, housing insecurity) can activate gambling. Furthermore, because gambling in the older homeless adult population is frequently hidden and regularly overlooked by service providers, it often continues unabated. Gambling in older adults can also contribute to the onset of first‐time homelessness. Large and rapid losses from high‐intensity gambling frequently characterize this route to homelessness. Such gambling is often triggered by major life events and changes (e.g. bereavement, job loss, relationship difficulties), and the outcomes are often worsened by the conduct of gambling operators and creditors. Conclusions: The link between gambling and homelessness in older adults is complex, with connecting mechanisms often contingent upon individual, interpersonal and structural conditions and contexts. There is potential for preventative and ameliorative action given many of the underlying conditions appear modifiable through policy intervention.